Viabilitas Mikrokapsul Biji Kefir Selama Penyimpanan Suhu Ruang - Kondong, D. J.; Taufik, E.; Arief, I. I. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
The process of encapsulation has done by various techniques such as the exstrusion, emulsion, spray dry, frezee dry and otherwise. The aimed of this study was to analysed the kefir grain microcapsule and its viability during storage in room temperature. The exstrusion technique was used to reach the optimum of biopolymer suspension and the percentage of kefir grains. Spray dry technique was used to produced kefir grains microcapsule before storaged in room temperature during 0, 15 and 30 days. The data were analyzed by using one-way analysis of variance (ANOVA) then followed by LSM and Duncan multiple range test. The analysis results showed that the exstrusion technique has been obtained the biopolymer suspension of sodium-alginate very significantly influence (P<0,01) to the yield and affected significantly (P<0,05) to the size, then the figure from microscope showed that shape of the beads were different. The results showed that the sodium-alginate was able to protect the microorganism cell by spray dry technique and so did the viability during storage in room temperature.